Characterization of the entrepreneurship education in humanities in higher education institutions in Mexico - Barragán-Perea, Efraín Alfredo (2023)
Modern society is increasingly aware that innovation and entrepreneurship play a transcendental role in achieving a sustainable economy that ensures the social well-being and employability of young people, hence the importance of promoting them through the university curriculum. For this reason, it is of great interest to determine the impact that universities and their educational models are having on entrepreneur training, since they may not be addressing the necessary skills. In this sense, the current study sought to characterize the entrepreneurial training of academic programs in the humanities at higher education institutions in Mexico that are members of the National Network of Schools and Faculties of Philosophy, Letters, and Humanities, as well as the necessary competencies for graduates to engage in entrepreneurial activity. For the methodological design, we used a descriptive method with a quantitative approach. We carried out a census of the member institutions to analyze the graduation profiles, curricular maps, subject objectives, and foundations of the 239 academic programs corresponding to the 36 member universities under the hypothesis that entrepreneurial training remains absent, which makes entrepreneurship difficult. We found a scarce development of academic competencies that favor the acquisition of knowledge and capacities for the entrepreneurship of its graduates.